PENERAPAN TEKNOLOGI AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN ILMU TAJWID HUKUM MAD BERBASIS MOBILE MENGGUNAKAN METODE MDA FRAMEWORK - Pradhana, Faisal Reza; Musthafa, Aziz; Putra, Firmana (J-Icon : Jurnal Komputer dan Informatika, 2023)
Al-Qur'an recitation learning activities at several Quran Education Parks (TPQ), including TPQ Al-Asyraf, are conducted through face-to-face methods where teachers and students interact directly. These interactions often involve using books as the primary source of learning materials. Based on the observation activities, it has been identified that the direct teaching method has certain weaknesses, particularly when working with Generation Z students who are accustomed to enjoying multimedia resources in their daily lives. This research aims to implement marker based augmented reality technology in learning Al-Quran recitation. The media is designed to be based on mobile Android, the source material is taken from the book on the science of Tajwid written by K.H Imam Zarkasyi, one of the founders of Pondok Modern Gontor Ponorogo. The learning media concept is designed in the form of an augmented reality game following the mechanical, dynamic and aesthetic (MDA) Framework method, while the media design follows the steps of the software development life cycle (SDLC) method with the waterfall approach. This research resulted in the application "Belajar Tajwid" which contains examples of readings from each Mad's law in the form of three-dimensional animation. Testing is carried out through 4 stages, namely testing application features using the Black box method yielding a value of 100% and testing the suitability of the application with various android devices. Testing was also carried out by distributing questionnaires to an expert on Al-Qur'an recitation material with a score of 95%, a media expert with 90% and to potential users with an average score of 92%, so that the AR Learning Tajwid media was categorized as "appropriate" to be used as a new teaching media in learning recitation of Al-Qur’an .